Diversity at the nanoscale: laser-oxidation of single-layer graphene affects Fmoc-phenylalanine surface-mediated self-assembly. Issue 12 (10th March 2023) - Schirmer, Johanna; Chevigny, Romain; Emelianov, Aleksei; Hulkko, Eero; Johansson, Andreas; Myllyperkiö, Pasi; Sitsanidis, Efstratios D.; Nissinen, Maija; Pettersson, Mika
Abstract : The secondary organization level of self-assembled Fmoc-phenylalanine is affected at the nanoscale by laser-oxidation of the graphene surface. Abstract : We report the effects of a laser-oxidized single layer graphene (SLG) surface on the self-assembly of amphiphilic gelator N -fluorenylmethoxycarbonyl-l -phenylalanine (Fmoc-Phe) towards an gel–SLG interface. Laser oxidation modulates the levels of hydrophobicity/hydrophilicity on the SLG surface. Atomic force, scanning electron, helium ion and scattering scanning nearfield optical microscopies (AFM, SEM, HIM, s-SNOM) were employed to assess the effects of surface properties on the secondary and tertiary organization of the formed Fmoc-Phe fibres at the SLG–gel interface. S-SNOM shows sheet-like secondary structures on both hydrophobic/hydrophilic areas of SLG and helical or disordered structures mainly on the hydrophilic oxidized surface. The gel network heterogeneity on pristine graphene was observed at the scale of single fibres by s-SNOM, demonstrating its power as a unique tool to study supramolecular assemblies and interfaces at nanoscale. Our findings underline the sensitivity of assembled structures to surface properties, while our characterization approach is a step forward in assessing surface–gel interfaces for the development of bionic devices.